2018
DOI: 10.1002/chem.201802387
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Heterogeneous Catalysts for CO2 Utilization by Using Dual Ligand ZnII/CdII Metal–Organic Frameworks

Abstract: Two-dimensional Zn /Cd -based dual ligand metal-organic frameworks (MOFs) {[M(CHDC)(L)]⋅H O} involving 4-pyridyl carboxaldehyde isonicotinoylhydrazone (L) in combination with flexible 1,4-cyclohexanedicarboxylic acid (H CHDC) as linkers have been synthesized by adaptable synthetic protocols including a green mechanochemical (grinding) method. Characterization, chemical/thermal stability, phase purity, and solid-state luminescent properties of both MOFs have been established by various analytical methods. Struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 105 publications
(205 reference statements)
0
13
0
Order By: Relevance
“…Metal-organic frameworks (MOFs) are currently among the most versatile materials, with crystalline porous structures built using organic linkers and metal cations. Since they were discovered [1], their applications were focused on biosensing, gas storage, separation, heterogeneous catalysis, and imaging [2,3,4,5,6,7,8]. More recently, their innovative biomedical applications as potential drug delivery nanocarriers are gaining increasing interest for the treatment of a variety of diseases [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) are currently among the most versatile materials, with crystalline porous structures built using organic linkers and metal cations. Since they were discovered [1], their applications were focused on biosensing, gas storage, separation, heterogeneous catalysis, and imaging [2,3,4,5,6,7,8]. More recently, their innovative biomedical applications as potential drug delivery nanocarriers are gaining increasing interest for the treatment of a variety of diseases [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, PXRD patterns of products obtained by water slurry (WS) and mechanochemical (BM and twin screw extrusion, TSE) are different from the same starting materials of Co(NO 3 ) 2 •6H 2 O and BPY [80] (Figure 10). Moreover, the ball milling method can introduce more defects into MOFs (Figure 11) [82,83], which makes their specific surface area larger and pore structure richer, which is conducive to its application in adsorption [23] and catalysis [44]. Li et al [23] demonstrated that HKUST-1 synthesized by mechanochemical method has a larger specific surface area and higher pore volume than HKUST-1 synthesized by hydrothermal method, and it has a medium-micro and double-pored structure, in which the micropores are conducive to the strong adsorption of adsorbate molecules, and the porous mesopores are conducive to the adsorption and diffusion of adsorbate molecules.…”
Section: Comparison Of Ball-milling and Solution Methodsmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are recognized as a promising platform for transforming carbon dioxide, 12–14 with fascinating features such as large surface areas, tailorable porosities, tunable configurations, and abundant metal active sites. 15 Metal clusters with coordinatively unsaturated sites (CUS) in MOF nodes generally serve as Lewis acidic sites for catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%